Effects of physical exercice over corporal fat predictor indexes: corporal mass index, waist-hip proportion and cutaneous folds - Oliveira Filho, Albertino de; Shiromoto, Rosana Naomi (Journal of Physical Education (Maringá), 2008)
The aim of this study was to verify alterations in corporal fat amount prediction indexes as a consequence of physical exercise, in assiduous individuals of programs offered in academies in the city of Maringá, state of Paraná, Brazil. The sample consisted of 68 subjects who practiced swimming, water aerobics, gymnastics or muscular exercice, being 38 women (age 29±6 years) and 30 men (age 28±8 years). The data was collected during the year of 2000. According to the results, both groups showed significant decrease of the variables related to corporal fat prediction (fat percentage, corporal mass index, waist-hip proportion) and significant increase in the thin corporal mass, independent of the exercise modality, allowing the conclusion that, besides aesthetic effects, physical exercises precticed with regularity and continuity act positively on aspects related to the individual’s life quality, bringing him/her closer to ideal health standards.